2017
DOI: 10.5014/ajot.2017.026724
|View full text |Cite
|
Sign up to set email alerts
|

International Educational Interactions and Students’ Critical Consciousness: A Pilot Study

Abstract: Online technologies facilitate connections between students around the world, but their impact on occupational science and occupational therapy students' critical consciousness about culture is underexplored. In this article we present research on five groups of occupational science and occupational therapy students across two cohorts at one Midwestern university. We used a pretest-posttest group design and the Multicultural Experiences Questionnaire to investigate the potential influence of students' exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The ten studies reported on activities that included students in nine different countries. Students from the United States were included in nine studies, South African students in three (Aldrich and Grajo, 2017; Aldrich and Peters, 2019; Wimpenny et al, 2016), Swedish students in two (Aldrich, 2015; Aldrich and Johansson, 2015), Indian students in two (Asher et al, 2014; Sood et al, 2014), with Philippines (Cabatan and Grajo, 2017), Cyprus (Psychouli et al, 2020), Greece (Zadnik et al, 2019) and Belgium and United Kingdom (Wimpenny et al, 2016) reported in one study each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ten studies reported on activities that included students in nine different countries. Students from the United States were included in nine studies, South African students in three (Aldrich and Grajo, 2017; Aldrich and Peters, 2019; Wimpenny et al, 2016), Swedish students in two (Aldrich, 2015; Aldrich and Johansson, 2015), Indian students in two (Asher et al, 2014; Sood et al, 2014), with Philippines (Cabatan and Grajo, 2017), Cyprus (Psychouli et al, 2020), Greece (Zadnik et al, 2019) and Belgium and United Kingdom (Wimpenny et al, 2016) reported in one study each.…”
Section: Resultsmentioning
confidence: 99%
“…The studies reported on qualitative data (Aldrich, 2015; Aldrich and Johansson, 2015; Aldrich and Peters, 2019; Cabatan and Grajo, 2017; Zadnik et al, 2019), quantitative data (Aldrich and Grajo, 2017) and a mix of qualitative and quantitative data (Sood et al, 2014). A total of 811 students were included across the ten studies presented (one study did not report on the number of students – Zadnik et al, 2019, and a number of studies only reported on US students – see Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Brown et al (2018) compared the academic virtue of national and international occupational therapy students in their work and identified possible adherents of student involvement in dishonest academic behavior. Aldrich and Grajo (2017) argued that to achieve effective collaboration between students and universities, there must be a high level of critical student awareness. Kinash et al (2019) proposed to establish university-stakeholder collaboration through education and production cluster of public-private partnership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of nursing competencies among health care providers and nursing students was considered a major solution in improving the quality of care and reducing inequality in health services. (Bernhard et al, 2015;Blanchet Garneau et al, 2017;Rebecca M. Aldrich, 2017) The nursing competency must be apprehended by nurses and nursing students. ("Cultural Competence: Annotated Bibliography 2009-2014 The clinical nursing competency framework to reach a national and international consensus required supervision.…”
Section: Introductionmentioning
confidence: 99%